Pengaruh Penggunaan Smartphone Terhadap Komunikasi Interpersonal Masyrakat Kota Batam - Desi Sariani (Universitas Putera Batam, 2014)
By looking at the effect of the use of smartphones on interpersonal communication Batam city communities with the aim to determine the effect of the use of smartphones on interpersonal communication Batam city communities. The purpose of this study was to determine how the use of smartphones in the city of Batam, to know how interpersonal communication community Batam city, describing the impact of the use of smartphones to interpersonal communication. Smartphone usage covers the File Manager, QuickOffice, Internet Browser, Zip and Pdf Manager, Calculator, Font Magnifie and covers interpersonal communication Interpersonal Perception, Self-Concept, Interpersonal Attractions, Interpersonal Relations. The research method used is descriptive research method and verikatif with a quantitative approach that is research is research that uses numerical data (numbers), which is then processed and analyzed to be concluded. So that research results obtained from this study is the level of smartphone use in high Batam city, it is affected by the use of smartphones can use the internet to communicate easily and quickly, which can chat, video calls etc, the level of interpersonal communication Batam city communities are dikriteria just high enough this happens less influenced by interpersonal attraction include common personal characteristics, emotional distress, low self-esteem, and social isolation and the use of Smartphones significantly affect interpersonal communication in Batam city communities.